Analyses on Economic and Trade Factors of Indonesia’s Export Value - Katon Wicaksono; Tu Yuanfen; Murtaza Darwishzada; Kyaw Htay (Journal of Economics, Bussiness and Management Issues, 2025)
Examines the crucial significance of the Regional Comprehensive Economic Partnership (RCEP) and trade facilitation measures in improving Indonesia's export performance.This study aims to evaluate the impact of customs efficiency, infrastructure development, and strategic investment on export value in Indonesia from 2002 to 2021. The study utilizes panel regression analysis to examine the degree to which advancements in these areas have facilitated the Indonesia's export sector. Research indicates that augmenting customs efficiency, upgrading infrastructure quality, and boosting investment in trade-related sectors are essential for reducing trade costs and expanding supply chain integration. Indonesia's export competitiveness by diminishing the time and expenses related to overseas trade. The  fundamental importance of Indonesia's involvement in the RCEP, which offers distinctive potential for the nation to enhance its trade facilitation initiatives, invigorate economic growth, and achieve improved integration into regional and global value chains. Being the one of largest free trade agreement globally, enables Indonesia to gain from improved market access, superior trading conditions, and a more advantageous regulatory framework. Comprehensive trade facilitation policies aimed at enhancing customs procedures, infrastructure, and investment in critical industries to promote export development. By focusing on these aspects, Indonesia can improve its trade competitiveness and attain continuous economic growth.